The Symbolic Interaction of Tandhe’ in Sumenep Madurese - Al Humaidy, Mohammad Ali; Ariwidodo, Eko (KARSA Journal of Social and Islamic Culture, 2020)
Local culture everywhere presents meaning space as a guideline for people’s lives, even the presence of tradition can be a medium of social transformation. The tandhe’ as one of the local cultural treasures in Sumenep Madura, emerged as an appreciation of past civilizations that believe that tandhe’ is not a mere spectacle but also as a communication medium that contains the values of goodness. Signs implicitly or explicitly important to learn because it often contains the essence of da’wah which calls on humans to remember God. Tandhe’ as a manifestation of local wisdom will be an effective communication medium for building communities when properly packaged, because cultural anomalies can occur at any time. The researcher uses a qualitative approach in the form of field research so that researchers can directly make observations and even participate in contributing ideas as feedback from informants ideas. The presence of tandhe’ has until now experienced a shift in the function and purpose of tandh’ itself. The ancient kings tandhe’ functioned as the media for the propaganda used by Walisongo in order to spread the teachings of Islam. The religious value of the tandhe’ began to fade because the lovers of the tandhe’ began to abandon the teachings taught by the Walisongo. Tandhe’ at the moment is more dominant in the nature of entertainment which aims only for worldly purposes only. Tandhe’ essentially has a symbolic communication used by Walisongo in preaching Islam to the community which is also a symbol of tirakat by human.